Timeless Wisdom in Investment and Its Approaches: Exploring Investment and Trading Strategies in the Indian Stock Market (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The paper takes a gander at investment and exchanging techniques the Indian financial exchange utilizing day by day information for CNX 100 organizations. The paper plots argumentation for the beta and obligation value proportion as critical factors to clarify Indian securities exchange investment and exchanging techniques. We are likewise building up a technique for exchanging on the financial exchange in accordance with the rule of mean inversion without supporting it. This examination utilizes methods of information investigations and infers that drawn out investment in stocks with low beta and low obligation value proportions yields expanded returns, albeit transient exchange high beta and high obligation value proportions yields exceptional yields over a brief period. The money related administrations area shows an exceptionally exceptional yield over a brief period and low long haul benefit contrasted with the normal stock return.